THE EFFECTIVENESS OF CASH WAQF REGULATION IN BANDA ACEH, INDONESIA: Examining of local peoples’ perspective - Dhilla Fadhilla; Mizaj Iskandar; Husni bin Abdul Jalil (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The purpose of this essay is to examine the community's opinions about cash waqf, its regulations, and its rules in relation to fiqh. One option available to Muslims in Banda Aceh City for allocating funds for worship is cash waqf. On a practical level, however, society is still unaware that cash waqf exists, and academics continue to hold differing views at the fiqh level. This is why a legislative method and a conceptual approach were used in the writing of this study. According to the study's findings, one type of transportable waqf is cash waqf. Classical and modern academics continue to disagree on the constitutionality of the legislation from a fiqh standpoint. The Waqf Law, Government Regulations Implementing the Waqf Law, Minister of Religious Affairs Regulations, and BWI Regulations are among the legal provisions in Indonesia that have made cash waqf acceptable. When it comes to Aceh, Qanun Baitul Mal is where monetary waqf is managed. In reality, certain Acehnese citizens, particularly those in Banda Aceh City, are aware of the cash waqf regulations, while others are not yet aware of them. Although Banda Aceh City residents are generally lenient and accept financial waqf, socialization initiatives by associated organizations are thought to be underutilized. Therefore, there must be a concerted effort to maximize community socialization and cash waqf product branding. Cash waqf requires a particular rule in the form of a qanun, which is an extension of the current Qanun Baitul Mal.